Maximum Likelihood Estimation and Testing of a Poisson Regression Model - Wan, J. Y.; Galecki, A. T. (Methods of Information in Medicine, 1992)
A Poisson regression model is proposed for the analysis of incidence rates presented in a two-way table classified by two categorical variables. It is shown that the likelihood function is the same as that using Glasser’s exponential covariate model. An algorithm is given to solve the maximum likelihood estimates of the regression parameters. The model is evaluated via deviance and the method is illustrated with an example. Some extensions of the model are discussed.
Keywords: Deviance; Exponential Regression; Incidence Rate; Poisson Regression